Case Report: Neoadjuvant and Adjuvant Crizotinib Targeted Therapy in Stage IIIA-N2 ALK-Positive Non-Small-Cell Lung Cancer - Xie, Xiao-Hong; Zhan, Ze-Jiang; Qin, Yin-Yin; Jiang, Ju-Hong; Yin, Wei-Qiang; Zheng, Rong-Hui; Li, Shi-Yue; Zhou, Cheng-Zhi (Frontiers in Oncology, 2021)
The treatment of anaplastic lymphoma kinase (ALK)-positive locally advanced non-small-cell lung cancer (NSCLC) is challenging because there is no randomized controlled trialhas been reported. The value of neoadjuvant and adjuvant targeted therapy remains unclear. Herein, we show that systemic treatment with ALK inhibitor crizotinib before surgery can provide the potential to cure the initially inoperable tumor. A 27-year-old man was diagnosed with a stage IIIAcT3N2M0 (7thUICC/AJCC)upper left lung adenocarcinomaharboring EML4-ALK fusion gene. Clinically, the patient had a large primary lesion adjacent to the pericardium and regional lymph node metastasis at the ipsilateral mediastinum. Poor tumor response was observed after3 cycles of chemotherapy (gemcitabine plus cisplatin), andupon multidisciplinary discussion, the patient was started with 250 mg crizotinibtwicedaily. Successive clinical examinations showed a progressive reduction of the lesions. After 2 months of therapy, the patient was downstaged to cT2aN2M0, then video-assisted thoracic surgery was performed and the final histopathological stage was ypT2aN2M0. The treatment with crizotinib(250 mg, qd)was continued more than 30 months post surgery and stopped until intracranial oligometastasis. The patient’s overall survival (OS) time is 68 months atlast follow-up. This case presented here supports the use of neoadjuvant and adjuvant treatment with ALK inhibitors in ALK positive locally advanced NSCLC.